Securing Nightlife: Media Representations of Public and Private Policing - Wadds, Phillip (2011)
There is ongoing ambivalence concerning door staff and crowd controllers in the night-time economy (NTE). Expanded private security is often acknowledged as a legitimate solution to the fear people experience in relation to urban night leisure. Yet there is significant official, media and public concern regarding the lack of regulation and governance over an industry still grounded in masculine aggression and with a long history of criminal association. Australian public and media concerns about ‘bouncers’ have grown dramatically in line with the expansion of night leisure, peaking after episodes such as the violent death of former cricketer David Hookes in 2004. This paper draws on the results of a fifteen-year archival search of The Sydney Morning Herald, The Daily Telegraph and other major Australian newspapers to analyse concerns regarding private security in a society that is increasingly anxious and sensitised to the risks associated with the city after dark.Sydney Institute of Criminology; School of Social Sciences at the University of Western Sydne